The Level of Digital Literacy Competencies of EFL Teacher in Bogor Senior High School - Nadhifa, Reynita; Santosa, Imam (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This research about digital literacy competence. The research was aim to determine the extent of the ability of EFL teachers in Bogor City Senior High Schools. To find out these abilities the researchers was categorized them into 3 levels, namely level 1 (Competence), level 2 (Usage), level 3 (Transformation) made by Allan Martin and collaborated with 8 elements of the basic digital literacy skills of Sarah Payton, namely Functional skills, Creativity, Critical thinking and evaluation, Cultural and social understanding, Collaboration, The ability to find and select information, Effective communication, and E-safety. This study used a qualitative method with a descriptive analysis approach. Data was collected by distributing questionnaires to schools in Bogor and there are 27 teachers from various school in Bogor who participated. From these 8 elements of digital literacy, researchers founded  there are 3 elements of Creativity and Cultural and Social Understanding. As many as 59% of teachers was still less Creativity, 57% did not understand culture and social in the digital world or Cultural and Social Understanding and 56% did not using critical thinking . Which those abilities must be improved.